Dapagliflozin partially restores reproductive function in MC4R KO obese female mice. Issue 2 (17th June 2022) - Cui, Ling; Tan, Chunlu; Huang, Lili; Wang, Weihao; Huang, Zhengxiang; Geng, Fang; Wu, Mengjun; Chen, Xiaolin; Cowley, Michael; Roelfsema, Ferdinand; Chen, Chen
Abstract : Obese women often have certain degree of reproductive dysfunction with infertility. Although the clinical impact of obesity on female infertility has been extensively studied, the effective and targeted treatment is still lacking. Melanocortin-4-receptor knock-out (MC4R KO) mouse is an over-eating obese model with hyperphagia, hyperinsulinemia, reduced growth hormone (GH), and insulin resistance. Dapagliflozin improved the metabolic and hormonal parameters in MC4R KO mice. MC4R KO female mice were treated with dapagliflozin for 14 weeks from 14-week age. Age-matched WT littermates and non-treated MC4R KO mice were used as control groups. Food intake was measured daily. Body weight was measured twice a week. Estrous cycles, GH, and luteinizing hormone (LH) profiles were measured. Selected tissues were collected at the end of experiments for gene expression profiles and hematoxylin–eosin staining. Regularity and mode of hormonal profiles were restored by the dapagliflozin treatment. Estrous cycle was partially normalized, number of CL was significantly increased, and the expression of Kiss1 and Gnrh1 in the hypothalamus and LH in the pituitary was markedly increased by the dapagliflozin treatment. It is conclsuded that dapagliflozin may recover LH and GH profiles partially through modification of relevant gene expression in the hypothalamus and pituitary, and result in an improved ovulation rate in obese mouse model. Dapagliflozin may therefore improve fertility in obese patients.